Advancing Action on the Implementation of Tobacco Tax Harmonization in the Organization of Eastern Caribbean States Countries - World Bank Group (World Bank, Washington, DC, 2018)
This study analyses the tax systems of five OECS countries (Antigua and Barbuda, Grenada, St. Kitts and Nevis, St. Lucia, and St. Vincent and the Grenadines). Taxes on tobacco, and therefore cigarette prices, vary widely across the five countries, and smuggling and tax evasion are genuine risks. The study assesses two possible harmonization scenarios, to estimate the possible impact of tobacco tax policy measures on tobacco use, and at the same time to expand the fiscal capacity of OECS governments through the mobilization of domestic resources. The simulations are modelled using the harmonization policies adopted at the OECS treaty of Basseterre. Comparisons are also made with other customs unions to identify regional best practices.